Preparation and Characterization of Natural Rubber/Polypropylene/Fatty Hyrazide-Octadecyl Ammonium Modified Clay Nanocomposites - Alosime, Eid Moneer (2008)
Fatty hydrazides (FH) which were synthesized from palm oil were used as one of the organic compounds to modify a natural clay (sodium montmorillonite). The clay modification was carried out by stirring the clay particles in an aqueous solution of a mixture of FH and octadecylammonium (ODA) by which the clay layer distance increases from 1.27 nm to 2.60 nm. The modified clay was then used in the preparation of the natural rubber/polypropylene (NR/PP) blend nanocomposites. The intercalation of the modifier in the clay layer was characterized by X-ray diffraction (XRD) and Fourier Transform Infrared (FT-IR). Elemental analysis was used to estimate the presence of FH and ODA in the clay. In the first part of the preparation, the nanocomposites were synthesized by melt mixing of the modified clay and a natural rubber (SMR CV60) using a two-roll-mill internal mixer. The compounded natural rubber was then mixed with organic peroxide-Luperox F-40P at 60 °C and cured at 130 °C using an electrical hydraulic hot press. Mechanical properties of the produced composites were then characterized. The results indicate that the presence of the modified clay has dramatically improved these properties. The crosslinked NR/clay nanocomposites were further characterized by XRD, Transmission Electron Microscopy (TEM) and Thermogravimetric Analysis (TGA). In the final part of the study, preparation of the nanocomposites was carried out by melt mixing of the modified clay with NR/PP in the ratio of 50:50 using the internal mixer. The study of mixing temperature, rotor speed and mixing time shows that under the following mixing conditions: temperature of 170 °C, 75 rpm of rotor speed and 10 minutes of mixing time, the composites with maximum tensile strength and elongation at break were obtained. The modified clay content to give maximum tensile strength is 1 php. The crosslinking of NR/PP, using Luperox F-40P to crosslink the rubber phase was also investigated. The compound was then cured in a hot press at 185 °C. The optimum concentration of Luperox F-40P to give maximum strength and elongation at break is 2.0 php. The tensile strength of Luperox F-40P crosslinked NR/PP/clay is higher compared to those of the unfilled crosslinked NR/PP/clay. The presence of 1 or 3 php of the modified clay into the Luperox F-40P crosslinked NR/PP increases its tensile strength. TGA study shows that crosslinked NR/PP/clay nanocomposites have higher decomposition temperatures in comparison with those of the crosslinked NR/PP/clay composites.